2014
DOI: 10.1556/avet.2014.024
|View full text |Cite
|
Sign up to set email alerts
|

Flax-seed oil and Lactobacillus plantarum supplementation modulate TLR and NF-κB gene expression in enterotoxigenic Escherichia coli challenged gnotobiotic pigs

Abstract: The present study analyses the effect of flax-seed oil rich in n-3 polyunsaturated fatty acids (PUFAs), the probiotic strain Lactobacillus plantarum -Biocenol TM LP96 and their combination on the expression level of selected Toll-like receptor (TLR) genes (TLR2, TLR4, TLR5, TLR9) and their downstream molecules (myeloid differentiation factor 88, MyD88; nuclear factor-κB, NF-κB) in the jejunum of gnotobiotic pigs challenged with enterotoxigenic Escherichia coli (ETEC). The results show that both immunomodulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We suggested that the administration of L. zeae LB1 was primarily implicated in competing for binding of TLR4 and TLR5, subsequently inhibiting the MyD88-dependent downstream pathway to downregulate the ETEC F4-induced production of pro-inflammatory cytokines. It had been reported by Chytilová et al that the pretreatment of L. plantarum significantly reduced the gene expression levels of TLR2 and TLR5 (but not TLR4) in the jejunum from ETEC F4-challenged piglets (O8:K88ab:H9:F4ab, without enterotoxin production). Here, we speculated that the potentiation of barrier integrity and amelioration of pro-inflammatory cytokines are likely attributed to the significant downregulation of TLR4 and TLR5 gene expression in L. zeae LB1-preincubated cells challenged with ETEC F4 bacteria.…”
Section: Discussionmentioning
confidence: 86%
“…We suggested that the administration of L. zeae LB1 was primarily implicated in competing for binding of TLR4 and TLR5, subsequently inhibiting the MyD88-dependent downstream pathway to downregulate the ETEC F4-induced production of pro-inflammatory cytokines. It had been reported by Chytilová et al that the pretreatment of L. plantarum significantly reduced the gene expression levels of TLR2 and TLR5 (but not TLR4) in the jejunum from ETEC F4-challenged piglets (O8:K88ab:H9:F4ab, without enterotoxin production). Here, we speculated that the potentiation of barrier integrity and amelioration of pro-inflammatory cytokines are likely attributed to the significant downregulation of TLR4 and TLR5 gene expression in L. zeae LB1-preincubated cells challenged with ETEC F4 bacteria.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, MyD88 deficient mice showed to be profoundly susceptible to infection (Issac et al, 2013). In weaning piglets, an increased level of MyD88 was already reported in enterocytes both in vivo and in vitro by several studies after challenge with an ETEC K88 strain (Chytilová et al, 2014;Finamore et al, 2014;Xu et al, 2014). TNFα is one of the most widely studied proinflammatory cytokine involved in numerous bacterial, parasitic and viral infections and was suggested as a biomarker of digestive pathologies in weaned piglets due to its correlation with villi/crypt ratio damages (Van Reeth et al, 2002;Gustavo Hermes et al, 2013;Barba-Vidal et al, 2017;López-Colom et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In generally, recognition of probiotic bacteria via TLRs in intestinal dendritic cells leads to their maturation and to release of cytokines, which coordinate the differentiation of naive T-helper cells (Th0) into mature Th1, Th2 or Th3/Treg subpopulations [64,65]. Probiotic bacteria do not cause inflammation, because they can regulate the immune response via a complex of mechanisms including reduction of some TLRs, inhibition of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways, and induction of TLR-negative regulators [66][67][68]. Application of probiotic Lactobacilli to SCI mice triggered a protective immune response in GALT and improved locomotor recovery [61].…”
Section: Promising Modulation Strategies Of Sci-induced Microglial Pl...mentioning
confidence: 99%
“…Another therapeutic approach in this area could be the application of ω-3 polyunsaturated fatty acids (ω-3 PUFAs), that are known to potentiate the immunomodulatory properties of probiotic lactobacilli via stimulation of bacterial adhesion to the intestinal wall [69,70] through their direct effect on the binding sites on the epithelial cells [71] and they are able to modulate TLR/NF-κB/cytokine level and proportion of lymphocyte subsets in the gut [67,68]. In the context of neurotrauma, supplementation of ω-3 PUFAs reduced oxidative stress, apoptosis and the levels of inflammatory mediators (TNFα, IL6) in rats with SCI [72].…”
Section: Promising Modulation Strategies Of Sci-induced Microglial Pl...mentioning
confidence: 99%